Climate and weather extremes in the UK: learning from the past and preparing for the future - Yule, Emma L. (The University of Edinburgh, 2024)
As global surface temperatures continue to rise, both the duration and intensity of heat- waves in Europe and the UK are expected to increase. The 2022 European summer heat- wave broke a number of temperature records and was associated with a range of societal impacts that were felt unequally across society. Heatwaves cause health impacts and fatalities with the 2003 European heatwave resulting in the loss of life of up to 70,000 people. However, compared to hazards with more visible consequences such as flooding events, the impacts of heatwaves can be overlooked leading them to be termed “silent killer” events. It is therefore important to improve our understanding of heatwaves and their impacts and how these may change in a warming world. The first part of this thesis explores what we can learn from past examples of heatwave events. Past events can provide points of reference to help with future decision making, allowing us to learn from the past. As extreme events are relatively rare by definition, by focusing on detecting early heatwaves, the sample of extreme events available for further analysis is extended. We detected and analysed historical heatwave events prior to 1927 in the UK and compared these to more recent events, including the 2022 heatwave event, allowing us to place modern events into historical context. We found that while there is a clear warming trend in the monthly data, the heatwave activity at the daily scale between 1878 and 1926 was considerable and in some cases comparable to modern heatwave events therefore, early events could be used as case studies to help us learn more about potential future heatwave events. We find that some impacts of early events are similar to those impacts today, such as the disparity in impacts of high and low-income regions. The second part of this thesis uses these examples of early heatwaves as case studies to analyse how the intensity of such events could change in the future. While many studies focus on the changing return periods of events in a warmer climate, fewer studies focus on a past event, from the early 20th century for example, and how it may look in a warmer climate based on a range of potential warming scenarios. We used a flow analogue methodology to explore what the early extreme events may look like in the future. We find that heat events such as the UK heatwave in 1923 increase in intensity at a similar rate to climatology as the global temperature increases, according to the models used. We find that at 4oC of global warming, the mean summer days during the 1923 heatwave in England is between 4.9 and 6.4 degrees warmer than pre-industrial levels across the three models used. Mean temperatures during analogous events, events of similar circulation patterns as 1923, over England range from 6.9 to 10.7oC higher than pre-industrial levels, for three different climate models used at 4oC. In addition, we comment on the limitations of this approach as well as the potential benefits, particularly as a communication tool to improve decision making around extreme heat. The interface between the scientific study of extreme event risk and how this is communicated and used by decision makers is currently a knowledge gap. The third part of this thesis investigates what tools, data and knowledge may aid adaptation decision makers while identifying what barriers exist in creating policies to increase resilience to extreme events. This research uses the Scottish public sector as a case study and we find that the majority of organisations are still at the planning phase of adaptation. We highlight key challenges including capacity and lack of organisational awareness of the need for adaptation and potential solutions to increase adaptation action in Scotland, including adaptation literacy training, tighter legislation and the use of boundary organisations or knowledge brokers. This research can help bridge the gap between climate science and decision makers by highlighting some key data requirements to help accelerate adaptation action and how it is monitored and evaluated. The novelty of this thesis is in the interdisciplinary approach taken, with contributions made throughout the impact chain, from hazard to risk and impacts. Overall, this inter- disciplinary research provides a method for learning from the past, while also exploring what is required to prepare for the future.
Keywords: climate change; heatwave; heatwave events; analogue methodology; adaptation; capacity challenges; planning for adaptation